UNC-64 and RIC-4, the plasma membrane-associated SNAREs syntaxin and SNAP-25, regulate fat storage in nematode Caenorhabditis elegans - Wu, Qiu-Li (Neurosci Bull, 2010)
OBJECTIVE: To investigate whether genes required for synaptogenesis and synaptic function are also involved in fat storage control in Caenorhabditis elegans. METHODS: Fat storage was examined in mutants of genes affecting the synaptogenesis and synaptic function. In addition, the genetic interactions of SNAREs syntaxin/unc-64 and SNAP-25/ric-4 with daf-2, daf-7, nhr-49, sbp-1 and mdt-15 in regulating fat storage were further investigated. The tissue-specific activities of unc-64 and ric-4 were investigated to study the roles of unc-64 and ric-4 in regulating fat storage in the nervous system and/or the intestine. RESULTS: Mutations of genes required for the formation of presynaptic neurotransmission site did not obviously influence fat storage. However, among the genes required for synaptic function, the plasma membrane-associated SNAREs syntaxin/unc-64 and SNAP-25/ric-4 genes were involved in the fat storage control. Fat storage in the intestinal cells was dramatically increased in unc-64 and ric-4 mutants as revealed by Sudan Black and Nile Red strainings, although the fat droplet size was not significantly changed. Moreover, in both the nervous system and the intestine, expression of unc-64 significantly inhibited the increase in fat storage observed in unc-64 mutant. And expression of ric-4 in the nervous system completely restored fat storage in ric-4 mutant. Genetic interaction assay further indicated that both unc-64 and ric-4 regulated fat storage independently of daf-2 [encoding an insulin-like growth factor-I (IGF-I) receptor], daf-7 [encoding a transforming growth factor-β (TGF-β) ligand], and nhr-49 (encoding a nuclear hormone receptor). Besides, mutation of daf-16 did not obviously affect the phenotype of increased fat storage in unc-64 or ric-4 mutant. Furthermore, unc-64 and ric-4 regulated fat storage probably through the ARC105/mdt-15- and SREBP/sbp-1-mediated signaling pathways. In addition, fat storage in unc-64; ric-4 was higher than that in either unc-64 or ric-4 single mutant nematodes, suggesting that unc-64 functions in parallel with ric-4 in regulating fat storage. CONCLUSION: The plasma membrane-associated SNAREs syntaxin/unc-64 and SNAP-25/ric-4 function in parallel in regulating fat storage in C. elegans, probably through the ARC105/mdt-15- and SREBP/sbp-1-mediated signaling pathways.